A Sociolinguistics of Mobility, Mundane Translinguistic Practices and Speakers’ Resourcefulness: Implications for ELT - Setiono Sugiharto (Universitas Islam Negeri (UIN) Mataram, 2021)
The idea of language deterritorialization has radically revolutionized the way we perceive, use and teach the entity we call language. Language has become porous and borderless, making its users capable of crossing borders at ease. Furthermore, language users can adeptly and creatively shuttle and mesh different linguistic resources either to index their new identities or to accomplish their communicative goals. Driven by the concept of mobility typified by the movement of people, ideas and objects from one real geographical or symbolic social space to other spaces, language is not only borrowed, but is also blended, remade, repurposed and even localized. Drawing upon the notion of ‘a sociolinguistic of mobility’, this article will illustrate the mundane sociolinguistic phenomena in diverse settings as exemplary instances of translinguistic practices, and then show that the quotidian linguistic practices in these settings reflect speakers’ resourcefulness. The article ends by discussing some implications of mobility for teaching English in a local context.